Three exopolysaccharides of the beta-(1 -> 6)-D-glucan type and a beta-(1 -> 3;1 -> 6)-D-glucan produced by strains of Botryosphaeria rhodina isolated from rotting tropical fruit - Vasconcelos, Ana Flora D. [UNESP]; Monteiro, Nilson K. [UNESP]; Dekker, Robert F. H.; Barbosa, Aneli M.; Carbonero, Elaine R.; Silveira, Joana L. M.; Sassaki, Guilherme L.; da Silva, Roberto [UNESP]; Corradi da Silva, Maria de Lourdes [UNESP] (Elsevier B.V., 2008)
Four exopolysaccharides (EPS) obtained from Botryosphaeria rhodina strains isolated from rotting tropical fruit (graviola, mango, pinha, and orange) grown on sucrose were purified on Sepharose CL-4B. Total acid hydrolysis of each EPS yielded only glucose. Data from methylation analysis and (13)C NMR spectroscopy indicated that the EPS from the graviola isolate consisted of a main chain of glucopyranosyl (1-->3) linkages substituted at 0-6 as shown in the putative structure below:[GRAPHICS]The EPS of the other fungal isolates consisted of a linear chain of (1-->6)-linked glucopyranosyl residues of the following structure:[GRAPHICS]FTIR spectra showed one band at 891 cm(-1), and (13)C NMR spectroscopy showed that a;] glucosidic linkages were of the p-configuration. Dye-inclusion studies with Congo Red indicated that each EPS existed in a triple-helix conformational state. beta-(1-->6)-D-Glucans produced as exocellular polysaccharides by fungi are uncommon. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Botryosphaeria rhodina isolates; Exopolysaccharides; beta(1 -> 6)-D-glucans; beta(1 -> 3 : 1 -> 6)-D-glucans; Triple-helix conformation